Common Knowledge and the Sidelining of Football Fans’ Rights and Civil Liberties - Jan Andre Lee Ludvigsen (Entertainment and Sports Law Journal)
In recent years, debates have revolved around the treatment of football supporters and supporters’ rights. Building upon Geoff Pearson’s idea of a ‘common knowledge’ on ‘football hooliganism’, this essay explores how this common knowledge is theoretically expandable and sustained via three important avenues speaking to the (i) control of data production; (ii) fantasy documents; and (iii) popular cultural manifestations. These collectively underpin not just a ‘common knowledge’; crucially, they assist the sidelining of fans’ rights across Europe.